2010
DOI: 10.1080/14786410903335174
|View full text |Cite
|
Sign up to set email alerts
|

The chemical structures, plant origins, ethnobotany and biological activities of homoisoflavanones

Abstract: This work reviews the four basic structural types of homoisoflavanones. The relationships between the various structures of homoisoflavanones and their plant origins, ethnobotany and biological activities are put into perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 63 publications
2
38
0
Order By: Relevance
“…These compounds are categorized into four types: 3-benzyl-4-chromanones, 3-benzylidene-4-chromanones, 3-benzyl-3-hydroxy-4-chromanones and scillascillins. 6 In general, these compounds are reported to show anti-inflammatory, anti-oxidative, anti-bacterial, anti-cancer, anti-histaminic, anti-viral, and anti-phosphodiesterase activities. Cremastranone ( 1 ), 5,7-dihydroxy-3-(3-hydroxy-4-methoxybenzyl)-6-methoxychroman-4-one, is a 3-benzyl-4-chromanone that has been isolated from the plants Muscari armeniacum , 7 Chionodoxa luciliae , 8 Scilla natalensis , 9 Merwilla plumbea , 10 and Cremastra appendiculata (D. Don) 11 ( 1 ; Fig.…”
mentioning
confidence: 99%
“…These compounds are categorized into four types: 3-benzyl-4-chromanones, 3-benzylidene-4-chromanones, 3-benzyl-3-hydroxy-4-chromanones and scillascillins. 6 In general, these compounds are reported to show anti-inflammatory, anti-oxidative, anti-bacterial, anti-cancer, anti-histaminic, anti-viral, and anti-phosphodiesterase activities. Cremastranone ( 1 ), 5,7-dihydroxy-3-(3-hydroxy-4-methoxybenzyl)-6-methoxychroman-4-one, is a 3-benzyl-4-chromanone that has been isolated from the plants Muscari armeniacum , 7 Chionodoxa luciliae , 8 Scilla natalensis , 9 Merwilla plumbea , 10 and Cremastra appendiculata (D. Don) 11 ( 1 ; Fig.…”
mentioning
confidence: 99%
“…Previous studies have revealed that the bulbs contain homoisoflavanones and stilbenoids (Bangani et al, 1999;Silayo et al, 1999). The chemical structures, plant origins, ethnobotany and biological activities of homoisoflavanones have been reviewed by Du Toit et al (2010). Studies by Bangani et al (1999) demonstrated 5 homoisoflavanones and 2 stilbenoids, while Silayo et al (1999) demonstrated 13 homoisoflavanones and 3 stilbenoids.…”
Section: Introductionmentioning
confidence: 97%
“…Its naturally occurring congeners ( 2–10 ), which contain either 5,7-dihydroxy-6-methoxy or 7-hydroxy-5,6-dimethoxy groups, have been reported already as shown in Figure 1 and most of them lack common names other than eucomnalin ( 9 ; autumnalin) and 3,9-dihydroeucomnalin ( 4 ; 3,9-dihydroautumnalin). Two review articles deal with the natural origins and structures of most homoisoflavonoids [7,8], and thereafter various studies of the homoisoflavonoids have been published [911]. Nevertheless, there have not been synthetic efforts towards such homoisoflavonoids since the synthesis of 4 and 9 was reported in 1971 [12].…”
Section: Introductionmentioning
confidence: 99%